Understanding assessment tasks: Learners' and teachers' perceptions of cognitive load of integrated speaking tasks for TBLT implementation. (December 2022) - Zhang, Weiwei; Zhang, Lawrence Jun
Abstract: TBLTis an educational approach to L2 learning and teaching where tasks constitute the main focus of classroom instruction. In its implementation, one of the major challenges facing teachers is the lack of empirical evidence for task design and selection relating to task complexity and the cognitive load imposed by tasks perceived by learners. To address the issue, we investigated EFL learners' and teachers' perceptions of cognitive load of integrated speaking tasks, one type of advocated tasks for TBLT, and factors that affect such perceptions within Robinson's Triadic Componential Framework as proposed by some scholars in the task research field. In a mixed-methods design, we collected data using a self-rating scale, a self-rating questionnaire and semi-structured interviews in the context of integrated speaking tasks for helping shed light on task design and selection criteria. Our analysis revealed that task complexity factors contributed to participants' perceptions of cognitive load, and in the four factors under investigation, prior knowledge was perceived as a stronger determinant of cognitive load than planning time, steps involved and task type. These findings provide empirical evidence for task design and selection in TBLT implementation, especially for the use of integrated speaking tasks in TBLT aiming at EFL speaking instruction. They also provide implications for L2 assessment.